Meningkatkan Kemampuan Pengajuan Masalah Serta Penyelesaian Masalah Matematika Melalui Pembelajaran Berbasis Masalah Pada Mahasiswa Jurusan Pendidikan Matematika STKIP “Tapanuli Selatan” Padang Sidempuan - Sinar Depi Harahap (Politeknik Negeri Padang, 2014)
Learning mathematics should be able to improve the abilityand creativity in learning mathematics, especially in solving mathematical problems. To improve theability of anappropriate learning need sand learning mathematical problem submissionis in accordance with the needs of students in facilitating the completion of (solution) of the mathematical problem significantly. To obtain data submission capability math problem students, the research for mulated the problemas follows: (a) How does the ability filing math problems before and after the learning seen from the stage before and during problem solving?,(b) How is the level of complexity of the questions asked of students according to the structure of language and mathematical relationships?, (c) how associations filing capability math problems with the ability of the settlement (solving) the mathematical problem?.To answer this problem conducted experimental research on mathematics semester students majoringin STKIP